Picturing personhood : brain scans and biomedical identity - Dumit, Joseph (In-formation series., 2004)
"By showing us the human brain at work, PET (positron emission tomography) scans are subtly--and sometimes not so subtly--transforming how we think about our minds. This book follows this remarkable and expensive technology from the laboratory into the world and back. It examines how PET scans are created and how they are being called on to answer myriad questions with far-reaching implications."